Architectural Modification of Conformal PEG‐Bottlebrush Coatings Minimizes Anti‐PEG Antigenicity While Preserving Stealth Properties. Issue 8 (25th March 2019) - Joh, Daniel Y.; Zimmers, Zackary; Avlani, Manav; Heggestad, Jacob T.; Aydin, Hakan B.; Ganson, Nancy; Kumar, Shourya; Fontes, Cassio M.; Achar, Rohan K.; Hershfield, Michael S.; Hucknall, Angus M.; Chilkoti, Ashutosh
Abstract: Poly(ethylene glycol) (PEG), a linear polymer known for its "stealth" properties, is commonly used to passivate the surface of biomedical implants and devices, and it is conjugated to biologic drugs to improve their pharmacokinetics. However, its antigenicity is a growing concern. Here, the antigenicity of PEG is investigated when assembled in a poly(oligoethylene glycol) methacrylate (POEGMA) "bottlebrush" configuration on a planar surface. Using ethylene glycol (EG) repeat lengths of the POEGMA sidechains as a tunable parameter for optimization, POEGMA brushes with sidechain lengths of two and three EG repeats are identified as the optimal polymer architecture to minimize binding of anti‐PEG antibodies (APAs), while retaining resistance to nonspecific binding by bovine serum albumin and cultured cells. Binding of backbone‐ versus endgroup‐selective APAs to POEGMA brushes is further investigated, and finally the antigenicity of POEGMA coatings is assessed against APA‐positive clinical plasma samples. These results are applied toward fabricating immunoassays on POEGMA surfaces with minimal reactivity toward APAs while retaining a low limit‐of‐detection for the analyte. Taken together, these results offer useful design concepts to reduce the antigenicity of polymer brush‐based surface coatings used in applications involving human or animal matrices. Abstract : The antigenicity of poly(oligoethylene glycol) methacrylate (POEGMA) bottlebrushes against anti‐PEG antibodies (APAs) is investigated for conformal POEGMA films grown from planar surfaces. By tuning the number of ethylene glycol (EG) repeats of POEGMA sidechains, it is shown that POEGMA brushes with two or three EG repeats minimize reactivity toward APAs while exhibiting resistance to nonspecific binding.